2005
DOI: 10.1021/jf040417e
|View full text |Cite
|
Sign up to set email alerts
|

Isolation of Tetra-acyl Sucrose Esters from Turkish Tobacco Using Supercritical Fluid CO2 and Comparison with Conventional Solvent Extraction

Abstract: Pure supercritical CO2 at various pressures and temperatures was used to effect the fractionation of tetra-acyl sucrose esters (SE) from dried, ground Turkish tobacco without any further pretreatment of the matrix. It was determined that SE cannot be extracted using low density CO2 (150 atm, 60 degrees C, and 0.62 gm/mL or 200 atm, 100 degrees C, and 0.49 gm/mL), whereas other analytes, which strongly interfere with the conventional solvent extraction of SE, can be easily removed under the same conditions. At … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0

Year Published

2005
2005
2014
2014

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 10 publications
1
14
0
Order By: Relevance
“…A previously described method (20) was used for all the extractions. In this method, 2 grams of dry tobacco were transferred to a 10 mL stainless steel vessel which was pressurized at 100 /C using pure CO 2 (250 atm).…”
Section: Extraction Of Sucrose Estersmentioning
confidence: 99%
See 1 more Smart Citation
“…A previously described method (20) was used for all the extractions. In this method, 2 grams of dry tobacco were transferred to a 10 mL stainless steel vessel which was pressurized at 100 /C using pure CO 2 (250 atm).…”
Section: Extraction Of Sucrose Estersmentioning
confidence: 99%
“…Our study differs from previously reported investigations in two respects: a) reversed phase liquid chromatography/electrospray mass spectrometry (RP-HPLC/MS) has been applied to non-derivatized sucrose esters and b) supercritical CO 2 has been used to extract the sucrose esters from the ground tobacco. Pure supercritical CO 2 at various pressures and temperatures was employed to effect fractionation of tetra-acyl sucrose esters from dried Oriental tobacco without any further pretreatment of the matrix (20). It was determined in this preliminary study that sucrose esters could not be extracted using low density (0.4-0.7 g/mL) CO 2 , but at this density other analytes which co-extract during the conventional solvent extraction of sucrose esters could be easily removed.…”
Section: Introductionmentioning
confidence: 99%
“…The workers were able to isolate four fractions from the HPLC separation with the last fraction being SE. More recently (14) this enriched tobacco fraction of SE from semi-preparative normal phase LC of the methylene chloride extract was chosen for characterization via HPLC-MS. Several types of SE were observed in the single tobacco that was studied that differed primarily in placement of the acyl functionality on either the glucose or the fructose fragment. In addition to acetyl, the other three observed acyl substitution patterns were governed by the presence of butyl, pentyl, and hexyl alkyl substituents.…”
Section: Resumementioning
confidence: 99%
“…Our sample of tobacco was extracted with a conventional liquid solvent using a method which has been described previously (14). A preliminary fraction of the extract was further isolated via semi-preparative normal phase HPLC using iso-octane/ethanol as the mobile phase.…”
Section: Resultsmentioning
confidence: 99%